Faucet: streaming de novo assembly graph construction - Rozov, Roye (Bioinformatics, 2018)
MOTIVATION: We present Faucet, a two-pass streaming algorithm for assembly graph construction. Faucet builds an assembly graph incrementally as each read is processed. Thus, reads need not be stored locally, as they can be processed while downloading data and then discarded. We demonstrate this functionality by performing streaming graph assembly of publicly available data, and observe that the ratio of disk use to raw data size decreases as coverage is increased. RESULTS: Faucet pairs the de Bruijn graph obtained from the reads with additional meta-data derived from them. We show these metadata—coverage counts collected at junction k-mers and connections bridging between junction pairs—contain most salient information needed for assembly, and demonstrate they enable cleaning of metagenome assembly graphs, greatly improving contiguity while maintaining accuracy. We compared Fauceted resource use and assembly quality to state of the art metagenome assemblers, as well as leading resource-efficient genome assemblers. Faucet used orders of magnitude less time and disk space than the specialized metagenome assemblers MetaSPAdes and Megahit, while also improving on their memory use; this broadly matched performance of other assemblers optimizing resource efficiency—namely, Minia and LightAssembler. However, on metagenomes tested, Faucet,o outputs had 14–110% higher mean NGA50 lengths compared with Minia, and 2- to 11-fold higher mean NGA50 lengths compared with LightAssembler, the only other streaming assembler available. AVAILABILITY AND IMPLEMENTATION: Faucet is available at https://github.com/Shamir-Lab/Faucet SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.